Splenium development and early spoken language in human infants. Issue 2 (21st October 2015) - Swanson, Meghan R.; Wolff, Jason J.; Elison, Jed T.; Gu, Hongbin; Hazlett, Heather C.; Botteron, Kelly; Styner, Martin; Paterson, Sarah; Gerig, Guido; Constantino, John; Dager, Stephen; Estes, Annette; et al.
Abstract: The association between developmental trajectories of language‐related white matter fiber pathways from 6 to 24 months of age and individual differences in language production at 24 months of age was investigated. The splenium of the corpus callosum, a fiber pathway projecting through the posterior hub of the default mode network to occipital visual areas, was examined as well as pathways implicated in language function in the mature brain, including the arcuate fasciculi, uncinate fasciculi, and inferior longitudinal fasciculi. The hypothesis that the development of neural circuitry supporting domain‐general orienting skills would relate to later language performance was tested in a large sample of typically developing infants. The present study included 77 infants with diffusion weighted MRI scans at 6, 12 and 24 months and language assessment at 24 months. The rate of change in splenium development varied significantly as a function of language production, such that children with greater change in fractional anisotropy (FA) from 6 to 24 months produced more words at 24 months. Contrary to findings from older children and adults, significant associations between language production and FA in the arcuate, uncinate, or left inferior longitudinal fasciculi were not observed. The current study highlights the importance of tracing brain development trajectories from infancy to fully elucidate emerging brain–behavior associations while also emphasizing the role of the splenium as a key node in the structural network that supports the acquisition of spoken language. Abstract : The association between developmental trajectories of language‐related white matter fiber pathways from 6 to 24 months of age and individual differences in language production at 24 months of age were investigated in 77 typically developing infants. The rate of change in splenium development varied significantly as a function of language production, such that children with greater change in fractional anisotropy from 6 to 24 months produced more words at 24 months (blue solid line in figure). These findings highlight the importance of tracing brain development trajectories from infancy to fully elucidate emerging brain‐behavior associations while also emphasizing the role of the splenium as a key node in the structural network that supports the acquisition of spoken language.